Distinct spatiotemporal patterns between fungal alpha and beta diversity of soil–plant continuum in rubber tree - Yaqing Wei; Zhixiang Wu; Guoyu Lan (Microbiology Spectrum)
ABSTRACT Plant-associated microbial communities strongly relate to host health and productivity. Still, our knowledge of microbial community spatiotemporal patterns in soil–plant continuum is largely limited. Here, we explored the spatiotemporal dynamics of fungal communities across multiple compartments (phyllosphere, leaf endosphere, soil, rhizosphere, rhizoplane, and root endosphere) of rubber tree in two contrasting seasons collected from Hainan Island and Xishuangbanna. Our results demonstrate that the fungal alpha and beta diversity exhibited distinct pattern; the alpha diversity is highly dependent on seasonal changes, while beta diversity only showed a geographical variation pattern. The season-specific environmental factors (e.g., climatic factors) were the most important factors in shaping fungal alpha diversity across the soil–plant continuum. Physicochemical properties explained some of the microbial beta diversity spatiotemporal variation observed, with leaf phosphorus (P) and soil available potassium (AK) likely being the main factors that drove the geographical variation. We further identified the variation of edaphic (e.g., AK) and leaf physicochemical factors (e.g., P) were mainly caused by regional sites (P < 0.05). Taken together, our study provides an empirical evidence that the distinct spatiotemporal patterns of alpha and beta diversity of rubber tree fungal diversity and significantly expand our understanding of ecological drivers of plant-associated microbial communities.IMPORTANCEPlants harbor diverse microorganisms in both belowground and aboveground compartments, which play a vital role in plant nitrogen supply and growth promotion. Understanding the spatiotemporal patterns of microbial communities is a prerequisite for harnessing them to promote plant growth. In this study, we show that the alpha and beta diversity of soil–plant continuum in rubber tree exhibited distinct spatiotemporal pattern. Alpha diversity is highly dependent on seasonal changes, while beta diversity only showed a geographical variation pattern. Climatic factors were the most important factors in shaping fungal alpha diversity. Leaf phosphorus (P) and soil available potassium (AK) were major drivers to induce geographical variation.